A comparison and optimization of methods and factors affecting the transformation of Escherichia coli - Verma, Chandra Shekhar (2015)
DNA manipulation routinely requires competent bacteria that can be made using one of numerous methods. To determine the best methods, we compared four commonly used chemical methods (DMSO, MgCl2–CaCl2, CaCl2 and Hanahan's methods) on frequently used Escherichia coli (E. coli) strains: DH5α, XL-1 Blue, SCS110, JM109, TOP10 and BL21-(DE3)-PLysS. Hanahan's method was found to be most effective for DH5α, XL-1 Blue and JM109 strains (P<0.05), whilst the CaCl2 method was best for SCS110, TOP10 and BL21 strains (P<0.05). The use of SOB (super optimal broth) over LB [Luria–Bertani (broth)] growth media was found to enhance the competency of XL-1 Blue (P<0.05), dampened JM109′s competency (P<0.05), and had no effect on the other strains (P>0.05). We found no significant differences between using 45 or 90 s heat shock across all the six strains (P>0.05). Through further optimization by means of concentrating the aliquots, we were able to get further increases in transformation efficiencies. Based on the optimized parameters and methods, these common laboratory E. coli strains attained high levels of TrE (transformation efficiency), thus facilitating the production of highly efficient and cost-effective competent bacteria.